From Ancient Omens to Statistical Mechanics. Essays on the Exact Sciences Presented to Asger Aaboe - Berggren, J.L. (1987)
xi-xv: Life and Work of Asger Hartvig Aaboe; xvii-xix: List of Publications of A.H. Aaboe